Unraveling the surface states related Stokes shift dependent electrocatalytic activity of N-doped carbon quantum dots for photovoltaic applications. (30th August 2021) - Ali, Mumtaz; Anjum, Aima Sameen; Riaz, Rabia; Bibi, Ayesha; Sun, Kyung Chul; Jeong, Sung Hoon
Abstract: Modulating the optical properties of carbon quantum dots (CQDs), such as blue to red emission, by varying the surface states is widely used for optical devices. However, the role of surface states in the electrocatalytic activity of CQDs remains incompletely elucidated. In this regard, we modulated the surface states by varying the synthesis solvents to obtain CQDs with varying Stokes shift: blue-, green-, and red-emissive CQDs denoted as BDs, GDs, and RDs, respectively. The electrocatalytic activity of these CQDs were investigated. To prevent aggregation-induced quenching of the electrocatalytic activity and enhance the conductivity, CQDs were grown on carbon nanotubes (CNT), which provide multidimensional charge transport channels. The RDs showed the largest Stokes-shift and better electrocatalytic activity than those of the GDs and BDs. The underlying mechanism for the superior electrocatalytic activity of the RDs was related to their effective band tuning, enhanced surface reactivity, and fast charge transfer. The performance of dye-sensitized solar cells employing RDs-modified CNT as counter electrode is comparable to that of a conventional Pt-based counter electrode. Graphical abstract: Image 1